Perencanaan dan Pentahapan Penambangan Nikel PT. Hillconjaya Sakti Site Indrabakti Mustika - Andi Maulana Yusuf; Yuliadi; Elfida Moralista (Jurnal Riset Teknik Pertambangan, 2024)
Abstrak. PT Hillconjaya Sakti operates a 512-hectare nickel mining area with a 2024 production target of 2,500,000 tons/year, an increase from 1,800,000 tons/year in 2023, necessitating updates in production planning and phase scheduling. Mining designs for the Longori, Silae, and Kolaka blocks follow Indonesian regulations and use Cut of Grade values: Lot 1 Ni 1.45, Lot 2 Ni 1.30, and Lot 3 Ni 1.25. Equipment availability is 86% with 54% utilization, achieving ore extraction efficiency of 71.1% and overburden removal efficiency of 74%. Excavator productivity reaches 240.26 tons/hour for ore and 275.98 BCM/hour for overburden, while dump trucks achieve 29.1 tons/hour and 55.17 BCM/hour, respectively. Reserves are estimated at 2,520,387 tons, adjusted to 2,515,753 tons with a stripping ratio of 1.44, and the 2024 disposal capacity is set at 3,618,793 BCM, supporting the company’s scaling and operational efficiency goals. Abstract. PT Hillconjaya Sakti is a nickel mining company with a 512 ha IUP area, aiming for a 2024 production target of 2,500,000 Tons/Year, up from 1,800,000 Tons/Year in 2023. This increase will impact the production plan and mine sequencing for 2024. The research aims to determine the production target, equipment productivity, reserve estimates based on the mine opening design, and mine sequencing plans.The mining designs were created in accordance with Indonesian mining regulations, including the Law No. 3 of 2020 and Ministerial Decree No. 1827 of 2018. The designs cover three mining blocks: Longori, Silae, and Kolaka, with classifications based on the company’s Cut of Grade values (Ni 1.45, Ni 1.30, and Ni 1.25). Mechanical equipment availability is 86%, with a 54% usage rate. The working efficiency for ore extraction is 71.1%, and for overburden removal, it's 74%. Productivity for ore extraction is 240.26 Tons/Hour for Backhoe and 29.1 Tons/Hour for Dump Truck. For overburden removal, productivity is 275.98 BCM/Hour for Backhoe and 55.17 BCM/Hour for Dump Truck. The estimated reserves based on the pit design are 2,520,387 tons. After completing the mine disposal plan, the reserves are reduced to 2,515,753 tons, with a stripping ratio of 1.44. The disposal capacity for 2024 is estimated at 3,618,793 BCM.